1998
DOI: 10.1007/s001340050698
|View full text |Cite
|
Sign up to set email alerts
|

Thiopental inhibits migration of human leukocytes through human endothelial cell monolayers in vitro

Abstract: In conclusion, we could show that thiopental is able to reduce the migration of PMNL through ECM significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This means that leucocyte migration had occurred already at the 4 h point into the wound in spite of surgery and balanced anaesthesia, since normal tissues do not contain leucocytes. Previous studies in adults have shown that anaesthetics can reduce leucocyte migration rate in vitro , and major surgery leads to increased leucocyte adherence, decreased neutrophil chemotaxis and dimished neutrophil delivery to areas of inflammation in adults ( 9,10), but that has not been tested earlier in small children.…”
Section: Discussionmentioning
confidence: 99%
“…This means that leucocyte migration had occurred already at the 4 h point into the wound in spite of surgery and balanced anaesthesia, since normal tissues do not contain leucocytes. Previous studies in adults have shown that anaesthetics can reduce leucocyte migration rate in vitro , and major surgery leads to increased leucocyte adherence, decreased neutrophil chemotaxis and dimished neutrophil delivery to areas of inflammation in adults ( 9,10), but that has not been tested earlier in small children.…”
Section: Discussionmentioning
confidence: 99%
“…During T cell activation, the actin cytoskeleton permits the formation of immune synapses and scaffolds for signal transduction molecules (Grakoui et al, 1999;Dustin and Cooper, 2000). Indeed, barbiturate application affects the microtubular assembly (Ventilla and Brown, 1976), and multiple reports describe reduced neutrophil chemotaxis or leukocyte migration through human endothelial cell monolayers following barbiturate exposure (Hofbauer et al, 1998;Nishina et al, 1998). Our results suggest that barbiturates directly affect these processes on the level of rac-1, whereas thiopental interacts differently.…”
Section: Discussionmentioning
confidence: 54%